2000
DOI: 10.1603/0022-0493-93.4.1276
|View full text |Cite
|
Sign up to set email alerts
|

Late-Instar European Corn Borer (Lepidoptera: Crambidae) Tunneling and Survival in Transgenic Corn Hybrids

Abstract: Field studies were conducted in 1996 and 1997 to determine injury by and survival of late-instar European corn borer, Ostrinia nubilalis (Hu¨ bner), on genetically altered Bacillus thuringiensis Berliner corn, Zea mays L. Cry1Ab events 176, Bt11, MON810, and MON802; Cry1Ac event DBT418; and Cry9C event CBH351 were evaluated. Plants of each corn hybrid were manually infested with two third-, fourth-, or Þfth-instar O. nubilalis. Larvae were held in proximity to the internode of the plant above the ear with a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 13 publications
3
37
0
3
Order By: Relevance
“…The larval survivorship (72-84% on leaf tissue after 6 d and 42.6-62.5% on intact plants after 21 d) observed in the current study was similar to that reported in other earlier studies (Walker et al, 2000;Wu et al, 2007;Ghimire et al, 2011). Larvae of all three genotypes of D. saccharalis on non-Bt corn plants also made a substantial number of entry/exit holes on the stalks and caused significant tunneling inside stalks.…”
Section: Discussionsupporting
confidence: 90%
“…The larval survivorship (72-84% on leaf tissue after 6 d and 42.6-62.5% on intact plants after 21 d) observed in the current study was similar to that reported in other earlier studies (Walker et al, 2000;Wu et al, 2007;Ghimire et al, 2011). Larvae of all three genotypes of D. saccharalis on non-Bt corn plants also made a substantial number of entry/exit holes on the stalks and caused significant tunneling inside stalks.…”
Section: Discussionsupporting
confidence: 90%
“…These studies focused on ECB baseline susceptibility to Bt toxins (Marçon et al, 1999), the initial frequency of alleles conferring Bt resistance in ECB populations , new methods for detecting these alleles in natural populations (reviewed in Venette et al, 2002), modeling and simulating the evolution of Bt resistance (Onstad and Guse, 1999;Davis and Onstad, 2000;Ives and Andow, 2002), the selection of Bt-resistant strains (Bolin et al, 1999), the genetics of Bt resistance (Huang et al, 1999a) and tests on whether Bt corn produced sufficient toxin to kill ECB (Walker et al, 2000).…”
Section: Collection Of New Empirical Data and Development Of Theoretimentioning
confidence: 99%
“…This behavior can expose the target pests to sublethal doses of Bt proteins through initial feeding in the Bt plant and subsequent feeding in the non-Bt plant (Andow, 2008). In addition, several studies showed that susceptibility of target pests to Bt proteins decreases throughout larval development (Ashfaq et al, 2001;Walker et al, 2000;Li et al, 2006;Armstrong et al, 2011). In this context, to optimize resistance management strategies, we evaluated the functional dominance of different aged larvae of Bt-resistant Spodoptera frugiperda in Bt maize expressing Vip3Aa20 protein.…”
Section: Introductionmentioning
confidence: 99%